Leveraging AI to Transform the Salesforce Sales Process: A Technical Overview - Aditya Pothukuchi (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This technical article explores the integration of Artificial Intelligence within Salesforce’s Customer Relationship Management platform, examining its transformative impact on sales process automation and optimization. The article investigates the architectural components, implementation strategies, and best practices across multiple organizations, focusing on lead generation, opportunity management, and customer engagement optimization. The article demonstrates significant improvements in sales productivity, operational efficiency, and customer relationship management through AI-driven solutions. The article encompasses data pipeline architecture, security frameworks, and compliance considerations, providing a comprehensive overview of modern enterprise AI implementation within CRM systems.